Local Community Involvement in Empowering Sustainable Development in South Remu Village, Sorong City, Southwest Papua - Ayswhara, Halizah; Zadah, Muhammad Rafi; Basri, La; Banggu, Masni (Universitas Muhammadiyah Yogyakarta, 2025)
Introduction: Community empowerment in sustainable development involves active participation in decision-making that affects their lives and environment. Purpose: To determine whether the community in South Remu Subdistrict is involved in the decision-making process related to sustainable development, as well as the obstacles they face in conveying their aspirations. Method: This study employed qualitative methods, utilizing structured interviews, observations, and literature reviews as data collection tools. Finding: This study shows that the South Remu District government has contributed to local community participation in development by conducting surveys, holding public consultations, facilitating working groups with stakeholders (BLK), and providing access to free nutritional services for infants and the elderly. Conclusion: Community participation in decision-making related to sustainable development in South Remu is essential to ensure that decisions are made in accordance with the needs and aspirations of the community and to reduce negative impacts on the environment.